Motor skills in pre-school education and affects to 5 year old children’s psychomotor development - Atike Yılmaz; Faruk Guven; Hakan Akdenız; Malik Beyleroglu; Ugur Senturk (Türk Spor ve Egzersiz Dergisi)
This study aimed to investigate the effect of the motor acquisitions placed in pre-school education program on the psychomotor development of 5 year-olds group children. In 2014-2015 school year, pre-school 5 year-old sex perimental group (n=55), control group (n=45) totally 100 children participated in. In order to measure the motor performances of control and experiment groups, the motor performance test protocol that, as pre-test, Morris, Atwater Williams and Will more performed in 1980 wasused. While the program of “Educational Play Activity Towards The Acquisitions About The Motor Development Placed in The Ministry of National Education Pre-School Program” wasapplied for the experimental group as 40 minutes for 2 days in a week for 8 weeks, Physical Activity wasappliedfor Control group as 10 minutes foreverymorning and 5 days in a week. The difference between pre-test and post-test was analysed by Paired-Samples t-test. The Differences between experimental group and control group were analysed by independent-Samples t-Test. The pre-test values of the experimental and control groups in the investigation were analysed by Independent Samples t-Test. The difference between control and experimental groups accordingto the analysis results of Promptness, Long Jump by Standingand Throwing Tennis Ball tests wasn’t found important statistically (p gt;0,05). Accordingto the analysis results of Balance, Speedand Catchingtests, significant difference was found statistically between the control andexperi mental group (p lt;0.05).The difference among the test averages of Long Jump by Standing and Throwing Tenis Ball of the control group wasn’t foundsignificant (p gt;0.05). The difference between pre-test and post-test belongingto experimental group was analysed by paired t-test. The difference among Promptness, Long Jump by Standing, Stand In Balance On OneFoot, Throwing Tennis Ball, Sprint and Catchingtests was foundsignificant statistically (p lt;0.05). It is understood that regularimplementation of Motor Acquisitions Placed in Pre-School Education Curriculum on 5 Year-Olds Group Children can develop the motor performances such as Balance, Speed and Catching skills significantly